2020
DOI: 10.3390/molecules25081830
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Lindenane-Type Sesquiterpenes from Lindera myrrha

Abstract: Two new lindenane sesquiterpenes were obtained from the roots of Lindera myrrha. These compounds were structurally elucidated by HRMS data, extensive NMR analyses, and comparison between experimental and theoretical 13C-NMR data. Myrrhalindenane A is the first monomeric seco-d lindenane displaying a non-rearranged, cyclohexanic C-ring. Myrrhalindenane B is the second occurrence of an angular lindenane-sesquiterpene related to a C6-C7 lactonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…On the other hand, natural antioxidants and many phytochemicals have been recently suggested as anti-cancer adjuvant therapies because of their anti-proliferative and pro-apoptotic properties [ 3 , 4 ]. Hence, the continuing search for anticancer agents/compounds from plants played a critical role to find the possible ways to have safe and to decrease the side effects induced by chemotherapy since natural herbal medicines have many advantages [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, natural antioxidants and many phytochemicals have been recently suggested as anti-cancer adjuvant therapies because of their anti-proliferative and pro-apoptotic properties [ 3 , 4 ]. Hence, the continuing search for anticancer agents/compounds from plants played a critical role to find the possible ways to have safe and to decrease the side effects induced by chemotherapy since natural herbal medicines have many advantages [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over several decades, around 200 new chemical compounds have been approved to fight cancer, 50% of which have originally come from natural products and their modifications, which are shown to be safe and have many advantages [ 11 , 12 ]. Plant-based therapy is considered to be a promising source for the development of new chemical compounds with potential bioactivities [ 9 , 13 , 14 , 15 , 16 ]. Along this line, Indigofera zollingeriana Miq is used in traditional medicine for treating various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Shatavari ( A. racemosus ) is a well-known Ayurvedic Rasayana that helps to slow down the aging process and boost immunity, neuropathy, and hepatopathy [ 68 ]. It is also used for the preparation of Chyawanprash [ 69 71 ]. Various studies have revealed that aqueous root extracts of A. racemosus exhibit anticancer activity, anti-inflammatory, antioxidant, and immunomodulatory properties [ 72 ].…”
Section: Selected Plants and Their Anticancer Activity Against Hepato...mentioning
confidence: 99%